PENGARUH PEMBERIAN INSENTIF DALAM MENINGKATKAN MOTIVASI KERJA KARYAWAN PERUSAHAAN JASA POS - Lite Lite; Sunarmie Sunarmie (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2016)
Incentive offer is one of the program an employer can apply to motivate the productivity of his employees who have capability and capacity in implementing their tasks according to their work performance. There are a few methods an employer can conduct to successfully run this program in which upgrading the human resources is considered as the most effective one.Research method used in this research study was a technique or method in searching, finding, collecting, and tabulating the primary and secondary data that are used as the factors in relation with the problems of the study to get reliability for the obtained data.According to the result of this research study about the effect of offering incentive in increasing employee motivation of PT. Pos Indonesia employees in Palangka Raya consisted of 4 (four) indicators, namely bonus, comission, deferred compensation, and social insurance. Therefore, the study research study resulted that incentive offer in motivating employee’s productivity at PT. Pos Indonesia Palangka Raya is on scale 327.5 which can be inferred that motivation incentive given to the employees at PT. Pos Indonesia Palangka Raya is sufficient, and is able to increase the work motivation of the employees in their productivity level. Work motivation of PT. Pos Indonesia employees according to 5 (five) indicators of physiological need, need for security, need for social ownership, self-esteem, and self-actualization resulted on score 312.3 in which can be concluded that the work motivation of PT. Pos Indonesia employees is relatively high, yet it still has to be maintained to keep improving productivity and work performance of the employees